Manufacturing System Design of a CNC Laser Engraver - Anrinal; Irfan Mandala Putra; Risky Oudio Viola (Jurnal Teknik Mesin, 2022)
This study aims to design manufacturing system of a CNC Laser Engraver Machine. The design starts from the laser module unit as input at the design stage of the 3-Axis CNC Machine to drive the laser. There are several important components in the production process of the CNC Laser Engraver machine, such as the Box Controller, the Laser Engraver Module unit, the Z-Axis unit, the X-Axis unit, and the Y-Axis unit. Bill of Material (BOM) design is very important to ensure the quantity and specification of materials, and the production of CNC Laser Engraver machines uses various types of production processes and ends with the assembly process. This CNC Laser Engraver machine was completed within 35 working hours, with a cost of Rp. 10,080,000,-.